PENGGUNAAN RAGAM MODIFIKASI PERMAINAN COLOURS BALL DALAM PEMBELAJARAN PJOK UNTUK MENINGKATKAN LITERASI NUMERASI SISWA SD NEGERI 1 SUKOREJO KEC. REJOSO KAB. NGANJUK - Prastyana, Brahmana Rangga; Astuti, Wiwik Retno; Maryanto, Tri (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
Numeracy literacy is important as a form of basic competency for students as preparation for responding to challenges in real life. This research was conducted to improve students' numeracy literacy through modifications to various color ball games. This type of research includes classroom action research using a two-cycle model. The research subjects were 16 students in class V of Sukorejo 1 State Elementary School, Rejoso District, Nganjuk Regency. The research instrument uses observation, skills tests, and knowledge tests. Data was analyzed using percentages with an achievement level of 75%. The results of the research illustrate that the use of modified color ball games can improve student learning outcomes in manipulative movement skills. The percentage of completeness increased from the original percentage of completeness in cycle 1 of 62%, increasing in cycle 2 to 87%. Next, related to numeracy literacy, there was also an increase from cycle 1 to cycle 2, namely from the Good to Very Good category. The conclusion of the research is that the application of modifications to various color ball games is effective in increasing manipulative movements and also increasing students' numeracy literacy at SDN 1 Sukorejo, Rejoso District, Nganjuk Regency